Evolving Paradigm of Radiotherapy for High-Risk Prostate Cancer: Current Consensus and Continuing Controversies. (23rd May 2016) - Juloori, Aditya; Shah, Chirag; Stephans, Kevin; Vassil, Andrew; Tendulkar, Rahul
Abstract : High-risk prostate cancer is an aggressive form of the disease with an increased risk of distant metastasis and subsequent mortality. Multiple randomized trials have established that the combination of radiation therapy and long-term androgen deprivation therapy improves overall survival compared to either treatment alone. Standard of care for men with high-risk prostate cancer in the modern setting is dose-escalated radiotherapy along with 2-3 years of androgen deprivation therapy (ADT). There are research efforts directed towards assessing the efficacy of shorter ADT duration. Current research has been focused on assessing hypofractionated and stereotactic body radiation therapy (SBRT) techniques. Ongoing randomized trials will help assess the utility of pelvic lymph node irradiation. Research is also focused on multimodality therapy with addition of a brachytherapy boost to external beam radiation to help improve outcomes in men with high-risk prostate cancer.